2023
DOI: 10.3390/polym15081922
|View full text |Cite
|
Sign up to set email alerts
|

An Investigative Study on the Structural, Thermal and Mechanical Properties of Clay-Based PVC Polymer Composite Films

Abstract: The present study aims to explore the impact of pristine and surfactant-modified clays (montmorillonite, bentonite and vermiculite) on the thermomechanical properties of a poly (vinyl chloride) (PVC) polymer film. Initially, clay was modified by employing the ion exchange method. The modification of clay minerals was confirmed by the XRD pattern and thermogravimetric analysis. Pristine PVC polymer film and clay (montmorillonite, bentonite and vermiculite)-based PVC polymer composite films were fabricated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Despite such reports, the effect of clays’ surface modification by quaternary ammonium ions on the mechanical properties of PVC-clay nanocomposites is not conclusive. Kumari et al [ 149 ] reported the opposite observation of Yin et al in the previous example [ 113 ].…”
Section: Characterization Of Pvc-clay Composite and Nanocompositementioning
confidence: 90%
See 1 more Smart Citation
“…Despite such reports, the effect of clays’ surface modification by quaternary ammonium ions on the mechanical properties of PVC-clay nanocomposites is not conclusive. Kumari et al [ 149 ] reported the opposite observation of Yin et al in the previous example [ 113 ].…”
Section: Characterization Of Pvc-clay Composite and Nanocompositementioning
confidence: 90%
“…Such widened utility stems from their accessibility, cost-effectiveness, high specific surface areas, cation-exchange ability, and multilayered organization. Nanoclays have shown exceptional effectiveness as reinforcing agents in polymer-based nanocomposites, with minor incorporation of clay enhancing the physicochemical properties of the polymer structure [ 26 , 27 ]. The manufacturing of clay-based polymer nanocomposites can result in the development of intercalated or exfoliated structures [ 28 ], which enhance characteristics such as thermal stability, mechanical strength, and barrier efficiency [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The weight loss due to the removal of organic species (i.e., surfactant molecule) was 12.77% over the temperature range of 130 °C−450 °C. A weight loss of 3.13% was observed between 450 °C and 800 °C due to the loss of the structural hydroxyl group within clay [34,35]. The TG curve of pure SO showed 3% weight loss between 30 °C and 200 °C, which was due to the physically adsorbed water.…”
Section: Thermogravimetric Analysis (Tga) Of Mt-and Omt-based Nano Pi...mentioning
confidence: 99%
“…However, the TG curve of OMt showed a lack of interlayer water and a substantial reduction in surface adsorbed water due to the presence of CPC, which further supports CPC intercalation into the clay interlayer and onto its surface. The weight loss due to the removal of organic species (i.e., surfactant molecule) was 12.77% over the temperature range of 130 • C−450 • C. A weight loss of 3.13% was observed between 450 • C and 800 • C due to the loss of the structural hydroxyl group within clay [34,35].…”
Section: Morphological Studiesmentioning
confidence: 99%
“…In the case of active cooling techniques, an additional device with parasitic power consumption is used to cool the PV system. Active cooling techniques mostly comprises of forced air flow or water flow on front or rear surfaces of PV panels [13]. The amount of water required for water cooling makes it more complex and it is unsuitable for arid regions where water scarcity is an issue [14].…”
Section: Introductionmentioning
confidence: 99%